Strategic management (Addison-Wesley, 1993)
The revised edition of this book now contains discusson of time-based competition versus cost-based competition, new coverage of total quality management, value-based strategies, concurrent design and manufacturing. It also looks at the application of expert systems as a strategic support tool. The text places the emphasis on the experiential approach in conducting case analysis for strategic management course. It uses worksheets to engage students in the study of course. The text includes all new cases and expanded coverage on topics such as organizational restructuring, competitor analysis, cost de-averaging and the use of information technology to gain a competitive advantage, global strategy, strategic alliances and generic competitive strategies. There is also emphasis on management aspects of strategy, on industry analysis, environmental analysis, on leadership and on the change process.